Damage Evolution of Frozen-Thawed Granite Based on High-Resolution Computed Tomographic Scanning - Li, Bo; Zhang, Guanghua; Wang, Gang; Qiao, Jiaxing (Frontiers in Earth Science, 2022)
Freeze-thaw damage of rocks is one of significant natural causes for geo-hazards such as collapse and rockfall in alpine areas. To explore damage evolution in granite in a freeze-thaw environment, specimens of granite in Nyingchi Prefecture, Tibet, China were collected as research objects. Saturated and dry rock specimens were subjected to cyclic freeze-thaw tests of 0, 36, 72, and 144 cycles and freeze-thaw damage of the rock was analyzed by combining computed tomography (CT) scanning and three-dimensional (3D) visualization. Results show that the peak stress of granite decreases to different extents with the increasing number of freeze-thaw cycles; compared with dry rock specimens, saturated granite deteriorates more significantly and shows obviously different stress–strain curves under loading. The moisture condition exerts significant influences on the degree of freeze-thaw damage to granite: after 144 freeze-thaw cycles, the mass loss rates of dry and saturated rock specimens are 0.06% and 0.44% and their loss rates of uniaxial compressive strength (UCS) reach 4.08% and 26.2%, respectively. Under freeze-thaw cycles, the frost heave of pore water causes initiation and development of micro-defects and new micro-cracks mainly develop along relatively weak areas such as inherent defects (pores and fractures) and boundaries between different mineral crystals, resulting in intergranular and transgranular cracking. For dry rock specimens, the non-uniform contraction and expansion of minerals therein are main causes for deterioration inside the rock. The freeze-thaw damage of rocks is calculated using the improved elastic modulus loss method. The damage development trend conforms to the strength deterioration trend and the pore development in the rock, reflecting the evolution of freeze-thaw damage to granite.